Paraoxonase-1 Regulation of Renal Inflammation and Fibrosis in Chronic Kidney Disease - Fatimah K. Khalaf; Chrysan J. Mohammed; Prabhatchandra Dube; Jacob A. Connolly; Apurva Lad; Usman M. Ashraf; Joshua D. Breidenbach; Robin C. Su; Andrew L. Kleinhenz; Deepak Malhotra; Amira F. Gohara; Steven T. Haller; et al. (MDPI AG, 2022)
Papraoxonase-1 (PON1) is a hydrolytic lactonase enzyme that is synthesized in the liver and circulates attached to high-density lipoproteins (HDL). Clinical studies have demonstrated an association between diminished PON-1 and the progression of chronic kidney disease (CKD). However, whether decreased PON-1 is mechanistically linked to renal injury is unknown. We tested the hypothesis that the absence of PON-1 is mechanistically linked to the progression of renal inflammation and injury in CKD. Experiments were performed on control Dahl salt-sensitive rats (SSMcwi, hereafter designated SS rats) and Pon1 knock-out rats (designated SS-Pon1em1Mcwi, hereafter designated SS-PON-1 KO rats) generated by injecting a CRISPR targeting the sequence into SSMcwi rat embryos. The resulting mutation is a 7 bp frameshift insertion in exon 4 of the PON-1 gene. First, to examine the renal protective role of PON-1 in settings of CKD, ten-week-old, age-matched male rats were maintained on a high-salt diet (8% NaCl) for up to 5 weeks to initiate the salt-sensitive hypertensive renal disease characteristic of this model. We found that SS-PON-1 KO rats demonstrated several hallmarks of increased renal injury vs. SS rats including increased renal fibrosis, sclerosis, and tubular injury. SS-PON-1 KO also demonstrated increased recruitment of immune cells in the renal interstitium, as well as increased expression of inflammatory genes compared to SS rats (all p < 0.05). SS-PON-1 KO rats also showed a significant (p < 0.05) decline in renal function and increased renal oxidative stress compared to SS rats, despite no differences in blood pressure between the two groups. These findings suggest a new role for PON-1 in regulating renal inflammation and fibrosis in the setting of chronic renal disease independent of blood pressure.